Hypomethylation of the Promoter Region of the Vascular Endothelial Growth Factor (VEGF) Gene and It’s Low Expression in Placenta as a Risk Factor for Preeclampsia - Godefridus Paulo Bay; A.A.N Jaya Kusuma; I Made Darmayasa; I Nyoman Bayu Mahendra; Putu Doster Mahayasa; Kadek Fajar Marta (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aimed to determine the association between hypomethylation of VEGF gene promoter region and low VEGF expression in the placenta as a potential risk factor for preeclampsia.Methods: An observational case-control study was conducted involving pregnant women with preeclampsia and normotensive controls. Placental tissue samples were collected and analysed for DNA methylation status of the VEGF gene promoter using quantitative real-time PCR. VEGF expression levels in placental tissue were measured using ELISA. Results: Significant hypomethylation of the VEGF promoter region was observed in placenta samples from preeclamptic women compared to controls. This finding correlated with decreased VEGF expression. These results indicate that reduced VEGF expression due to promoter hypomethylation may impair placental vascularization, contributing to preeclampsia.Conclusions: Hypomethylation of the VEGF promoter and subsequent reduction in placental VEGF expression may serve as early biomarkers to predict preeclampsia. These results highlight the importance of epigenetic regulation in preeclampsia pathogenesis and suggest potential targets for early diagnosis and intervention.Hipometilasi Regio Promoter Gen Vascular Endothelial Growth Factor (VEGF) dan Ekspresi Vascular Endothelial Growth Factor (VEGF) yang Rendah pada Plasenta sebagai Faktor Risiko PreeklampsiaAbstrakTujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara hipometilasi pada daerah promoter gen VEGF dan rendahnya ekspresi VEGF di plasenta sebagai faktor risiko potensial terjadinya preeklampsia.Metode: Penelitian observasional dengan desain kasus-kontrol ini melibatkan ibu hamil dengan preeklampsia dan kontrol normotensif. Sampel jaringan plasenta dikumpulkan dan dianalisis untuk menentukan status metilasi DNA pada daerah promoter gen VEGF menggunakan quantitative real-time PCR. Tingkat ekspresi VEGF dalam jaringan plasenta diukur menggunakan metode ELISA.Hasil: Didapatkan hipometilasi yang signifikan pada daerah promoter gen VEGF pada jaringan plasenta ibu dengan preeklampsia dibandingkan kelompok kontrol. Temuan ini berkorelasi dengan penurunan ekspresi VEGF. Hasil tersebut menunjukkan bahwa penurunan ekspresi VEGF akibat hipometilasi promoter dapat mengganggu vaskularisasi plasenta, sehingga berperan dalam patogenesis preeklampsia.Kesimpulan: Hipometilasi pada daerah promoter gen VEGF dan penurunan ekspresi VEGF di plasenta dapat berfungsi sebagai biomarker awal untuk memprediksi terjadinya preeklampsia. Hasil ini menyoroti pentingnya regulasi epigenetik dalam patogenesis preeklampsia serta membuka peluang untuk diagnosis dini dan intervensi yang lebih tepat.Kata kunci: Preeklampsia, VEGF, Hipometilasi, Plasenta, Epigenetik